Researcher: A User Extensible Statistical System - Marciniak, Thomas A. (1988)
Researcher is a software package for IBM PC compatible computers for clinical research data management, statistical analysis, and graphics. It is written in compiled BASIC, and all source programs are available in the public domain. We describe its features, emphasizing those that facilitate the incorporation of additional statistical analyses.